2D and 3D seismic investigations for Stage 1 and 2C - Gurevich, Boris; Pevzner, Roman; Urosevic, Milovan; Kepic, Anton; Shulakova, V.; Caspari, Eva; Lebedev, Maxim (CSIRO Publishing, 2014)
Carbon capture and geological storage (CCS) is presently the only way that we can make deep cuts in emissions from fossil fuel-based, large-scale sources of CO2 such as power stations and industrial plants. But if this technology is to be acceptable to the community, it is essential that it is credibly demonstrated by world-class scientists and engineers in an open and transparent manner at a commercially significant scale. The aim of the Otway Project was to do just this. Geologically Storing Carbon provides a detailed account of the CO2CRC Otway Project, one of the most comprehensive demonstrations of the deep geological storage or geosequestration of carbon dioxide undertaken anywhere. This book of 18 comprehensive chapters written by leading experts in the field is concerned with outstanding science, but it is not just a collection of scientific papers – it is about “learning by doing”. For example, it explains how the project was organized, managed, funded and constructed, as well as the approach taken to community issues, regulations and approvals. It also describes how to understand the site: Are the rocks mechanically suitable? Will the CO2 leak? Is there enough storage capacity? Is monitoring effective?